Urban climate resilience in Indian cities: current practices and challenges in mainstreaming adaptation to climate change - Jha, Maulsri; ., . (International Journal of Engineering and Technology, 2018)
The urban population in India is expected to increase by about 500 million in the next 50 years, which would catapult Indian urban regions towards climate change related disasters such as extreme temperatures and precipitation, droughts, river and inland flooding, storm surges and coastal flooding, sea-level rise and other environmental risks. Large gaps exist in the demand and supply of infrastructure and services in urban regions. A radially outward approach is necessary for cities to integrate mitigation and adaptation policies into their urban design and planning philosophy. Municipal authorities are already grappling with shortages in basic infrastructure and therefore, mainstreaming adaptation and resilience is not high on the priority list of government bodies in the country. There is a need to adopt a pan-sectoral approach to upgrade mitigation and adaptation policies and to motivate actors from different sectors for a holistic integration of urban resilience into the design and planning fabric of urban regions in India. Urban climate vulnerability of India is not only a technical challenge, but is also deeply rooted into the social and cultural ethos of the country; we must realize that resilience building in the nation cannot be merely a physical planning exercise but has to be socially equitable as well. Through this paper, an effort has been made to examine the current structure and practices which are in place in Indian cities for the purpose of mainstreaming disaster adaptation. For this purpose, the paper analyses emerging lessons, experiences and limitations of resilience design and planning in select cities of Asia associated with the Asian Cities Climate Change Resilience Network (ACCCRN), a network which is dedicated towards identifying vulnerabilities and mainstreaming agendas associated with resilience design and planning and disaster mitigation and adaptation. Several Indian cities are a part of this network as well. Internationally, commendable and exhaustive work has been done for mainstreaming adaptation to climate change in the primary design and planning of cities, and this is indeed helpful for formulating suitable standards which could be applicable to the architectural policies for a resilient urban India. Additionally, this paper would also analyse and examine various challenges and roadblocks that are faced by urban governance in strengthening management and mitigation practices in India to deal with hazards. Finally, the paper would end by describing possible adaptation frameworks for encouraging efficient resilience architecture and planning in urban India.Â Â Â